ANALISA KINERJA KEUANGAN PADA KOPERASI PEGAWAI NEGERI (KPN) SWAKERTA PADA DINAS KOPERASI UMKM PROVINSI JAMBI - Arna Suryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
This research was conducted to find out how the financial performance of the cooperative civil servants (KPN) Swakerta at Dinas Koperasi SMEC Jambi province in raising the rest of the business results (SHU) as well as the ability to know how the financial performance cooperative public servants (KPN) Swakerta at Dinas Koperasi SMEC jambi province in fulfilling the obligations of both short term and long term review of financial ratio analysis. This research is descriptive research with data types used are secondary data, obtained directly from KPN Swakerta Cooperative Agency of SMALL MEDIUM ENTERPRISES in Jambi province with a period of pemangamatan years 2011 to 2015. Methods of analysis used is ratio analysis based on the decision of the Minister of cooperatives and small and medium enterprises no. 06/Per/m. KUKM/V/2006 performance assessment guidelines of the cooperative. Based on the results of research financial performance based on the ratio of earning ratios as measured by return on assets (ROA) acquired for 7.66% with standard 7%-< 10% performance dikatergori good and based on return on equity of 10.11% with standard 9%-< 15% performance categorized quite well. Based on liquidity ratio obtained 752.61% with standard < 125 s/d > 325% categorized poorly performing. While the financial performance based on solvency ratio is categorized very well based on the debt to asset ratio (DAR) and debt to equity ratio (DER) with 40% and standard < < 70%. To improve the performance of financial liquidity ratio of the cooperative civil servants (KPN) Swakerta at Dinas Koperasi SMEC Jambi province should have to raise and add to the amount of debt and further enhance the smooth smooth asset to be able to optimize lancarnya funds so that it could reduce the funds that are idle. For subsequent researchers are advised to add the variable or ratio-a ratio more as well as assess the performance of cooperatives are more comprehensive.Keywords: cooperatives, financial statements, ratio analysis, financial performance